PENGARUH FINANCIAL SLACK TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Sofina Pasaribu, Maria; Haryanto, Mulyo (Faculty of Economics and Business Diponegoro University, 2018)
The new literature abaout financial slack is still rarely. Financial Slack is a phenomenon that occurs where the availability of corporate finance exceeds their needs which are then used to help finance the organization The purpose of this reseach is to determine the relation between financial slack with financial performance on manufacturing companies in Indonesian Stock Exchange. Company performance as dependent variable, while independent variables are HDFS (high discretionary financial slack), LDFS (low discretionary financial slack), AFR (availability for financial resources), DFR (demand for financial resources), and TFS (transitory financial slack).The sample in this research is manufacturing companies in Indonesian Stock Exchange during period 2014-2016. The sampling method in this research is purpose sampling. This research is based on organizational and behavioral theory and analyzed using multiple regression.The result shows that all the independent variables that represent financial slack have significant and positif relation with performance, so all variables accepted, which means the financial slack can increase the performance on the manufacturing companies. We will suggest that in future research can to follow the variable because it is a good measure of financial slack indicator that related with performance.